Whom you are with will make your travel greener. (October 2021) - Wang, Bo; Shi, Han; Sun, Kaining; Guo, Hongwei; Zhang, Shaochen; Wang, Zhaohua
Highlights: Family relationship center has a strong impact on family members travel model preference. The scarcity of family resources and the distribution mechanism can influence travel behavior. There is obvious reciprocity in group travel (strong-tie network). Community's low-carbon atmosphere has a greater impact on people with local account. Abstract: Accurate identification of the determinants affecting public low-carbon travel is crucial to the design and evaluation of environmental policies. Current studies mainly focus on individual attributes, missing the effect of social relations on travel behavior decisions, especially in the context of Chinese culture. Our study based on a large-scale transportation survey (642 communities, 43, 768 households and 282, 933 travel records), using logit regression to provide an empirical assessment of strong and weak ties on travel behavior. The results indicate that (1) the impact of household head on family members mainly focuses on cultural awareness and resource level; (2) There is obvious reciprocity in group travel (strong-tie network). (3) In the weak ties represented by neighborhood relations, the stronger the community's low-carbon atmosphere is, the greater the probability of members' low-carbon travel behavior. Our research provides a new perspective to improve the likelihood of low-carbon travel behavior for residents under Chinese society.